SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS WEB PADA TOKO KOSMETIK ZAVISH MS GLOW JAKARTA - Muhammad Abby Hartadi (2022)
In the current era of globalization, information technology plays an important role in people's lives. With the development of information technology, people's work has become easier. By using information technology in the business world, it will have a positive impact on the business operations that are built. The process of inputting goods at the Zavish MS Glow Jakarta cosmetic shop is still carrying out manual processes for managing goods and reporting processes that still use the ledger. Based on this, the author will design and also create a web-based inventory information system to facilitate the work of Zavish MS Glow Jakarta in the process of managing goods. The method used by the author is the Waterfall Method with problem identification using the PIECES method, the PHP programming language, and the database used is MYSQL, and ends with a trial test using the black box testing method. With the development of this web-based application, the Zavish MS Glow Jakarta cosmetic store has been able to manage goods and can also print reports of incoming and outgoing goods easily.